In-Silico Design and Evaluation of the Anti-Wolbachia Potential of Boron-Pleuromutilins - Fabian Audu Ugbe; Gideon Adamu Shallangwa; Adamu Uzairu; Ibrahim Abdulkadir (Borneo Journal of Pharmacy, 2023)
Filariasis (Lymphatic filariasis and Onchocerciasis) is a common neglected tropical disease caused by parasitic nematodes called filarial worms, which often host the Wolbachia bacteria. A good treatment approach seeks Wolbachia as a drug target. Here, a computer-aided design of some boron-pleuromutilin analogs was conducted using the ligand-based drug design approach while performing molecular docking investigation and pharmacokinetics analyses to evaluate their drug-likeness properties. The newly designed compounds (49a, 49b, and 49c) showed improved inhibitory activities (pEC50) over those of the template and the clinically relevant pleuromutilins (retapamulin and lefamulin) in the order; 49b (pEC50 = 9.0409) > 49c (8.8175) > 49a (8.5930) > template (49) (8.4222) > retapamulin (6.7403) > lefamulin (6.1369). Standard docking performed with OTU deubiquitinase (6W9O) revealed the order of binding energies; 49c (-88.07 kcal/mol) > 49b (-84.26 kcal/mol) > doxycycline (-83.70 kcal/mol) > template (-82.57 kcal/mol) > 49a (-78.43 kcal/mol) > lefamulin (-76.83 kcal/mol) > retapamulin (-76.78 kcal/mol), with the new compounds all showing good pharmacological interactions with the receptor’s amino acids. The new analogs were also predicted to be orally bioavailable with better pharmacokinetic profiles than the template, retapamulin, lefamulin, and doxycycline having no more than one violation of Lipinski’s ROF. Therefore, the newly designed compounds could be considered potential anti-filarial drug candidates.